If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 = -30 + 6 Reorder the terms: 3 + x = -30 + 6 Combine like terms: -30 + 6 = -24 3 + x = -24 Solving 3 + x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = -24 + -3 Combine like terms: 3 + -3 = 0 0 + x = -24 + -3 x = -24 + -3 Combine like terms: -24 + -3 = -27 x = -27 Simplifying x = -27
| -94=-6(b+4)-4b | | 12x-4=-68 | | 2(x-6)=x+14 | | 11x-88-11=27x-275 | | 10=12x-11x-17 | | -1(f+20)=7 | | 75=3(-12x-3) | | -2(1+7x)+5(x-5)=10x-10-2x | | -7x=-34 | | 2x^3y-10x^2y-6xy= | | 2x+x-9=-45 | | 5u^2-240=0 | | -8x-29+10x=9 | | f(x)=4e^3x+2 | | 2sinx-6=0 | | -28+2n=4(6n-7) | | 5h^2+400=0 | | 6y=7+5y | | X^2-8*x+7=0 | | 3x-5x=23-15 | | 13-4x-7x=18x+14 | | m^6=16m^4 | | 3(x-4)2=3(x-1)-7 | | 32x+5=3x-3 | | 7-3x=2x+27 | | pH=-log[5.7*10(-4)] | | 11x-85+x=167 | | 2(8x+60)=5(9x-10) | | 12x-3x-17=-12x+27 | | 7-3x=2+27 | | -10(-3-9m)=-5(11m-6) | | 2(2+b)+(2b)=900 |